The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Journal of Cancer Research and Therapeutic Oncology 2016
DOI: 10.17303/jcrto.2016.103
|View full text |Cite
|
Sign up to set email alerts
|

Primary Cultures Derived From Bovine Papillomavirus-Infected Lesions As Model To Study Metabolic Deregulation

Abstract: Bovine papillomavirus (BPV) is the etiological agent of bovine papillomatosis, disease characterized by the presence of multiple papillomas that can regress or to progress to malignances. Due to the pathological similarities with the human papillomavirus (HPV), BPV is considered a prototype to study the papillomavirus-associated oncogenic process. Although it is clear that both BPV and HPV can interact with host chromatin, the interaction of these viruses with cell metabolism remains understudied due to the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 24 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…In this sense, studies have been shown that the HPV-16 E6* oncoprotein has a pro-oxidant action [74,210]. Similar results were described in study involving the BPV-1 E6 oncoprotein [76]. Moreover, both BPV E6 [88] and HPV E6/E7 oncoprotein can lead to cytogenic damages [114,115], resulting in genomic instability, which can result in the CSC development.…”
Section: Hpv and Metastasismentioning
confidence: 74%
See 3 more Smart Citations
“…In this sense, studies have been shown that the HPV-16 E6* oncoprotein has a pro-oxidant action [74,210]. Similar results were described in study involving the BPV-1 E6 oncoprotein [76]. Moreover, both BPV E6 [88] and HPV E6/E7 oncoprotein can lead to cytogenic damages [114,115], resulting in genomic instability, which can result in the CSC development.…”
Section: Hpv and Metastasismentioning
confidence: 74%
“…The authors also showed that HPV-16 E6 promotes the STAT3 activation [259]. The STAT3 activation was also described in cell line derived from bovine esophageal carcinoma co-infected by BPV-1, 2 and 4, suggesting that the STAT3 phosphorilation is a consequence of oxidative stress induced by E6 oncoprotein [76]. Interestling, Araldi et al [182] verified that BPV-infected cells from bovine fibropapilloma and esophageal carcinoma exhibit morphological alterations, including the loss of cell polarity, and increase the expression levels of Oct-3/4, suggesting that the EMT onset in pre-neoplastic lesions (fibropapillomas).…”
Section: Hpv and Metastasismentioning
confidence: 84%
See 2 more Smart Citations